Using Benefit-Based Tailored Treatment to Improve the Use of Antihypertensive Medications - Sussman, Jeremy (2013)
BACKGROUND: Current guidelines for prescribing antihypertensive medications focus on reaching specific blood pressure targets. We sought to determine if antihypertensive medications could be used more effectively by a treatment strategy based on tailored estimates of cardiovascular disease (CVD) events prevented. METHODS AND RESULTS: We developed a nationally representative sample of American adults aged 30 to 85 years with no history of myocardial infarction, stroke, or severe congestive heart failure using the National Health and Nutrition Examination Survey III. We then created a simulation model to estimate the effects of 5 years of treatment with a treat-to-target (TTT, treatment to specific blood pressure goals) and benefit-based tailored treatment (BTT, treatment based on estimated CVD event reduction) approaches to antihypertensive medication management. All effect size estimates were directly derived from meta-analyses of randomized trials. We found that 55% of the overall population of 176 million Americans would be treated identically under the two treatment approaches. BTT would prevent 900,000 more CVD events and save 2.8 million more QALYs, despite using 6% fewer medications over 5 years. In the 45% of the population treated differently by the strategies, BTT saves 159 QALYs per 1000 treated vs. 74 QALYs per 1000 treated by TTT. The findings were robust to sensitivity analyses. CONCLUSIONS: We found that benefit-based tailored treatment was both more effective and required less antihypertensive medication than current guidelines based on treating to specific blood pressure goals.